Narrative stories of high risk sexual behaviors among adolescents in Makassar City - Indra Fajarwati Ibnu; Chatarina Umbul Wahyuni; Shrimarti Rukmini Devy (Journal of Public Health Research, 2020)
Background: Dating behavior by some Indonesian adolescents is against the social norms of the society, showing moral gaps and psychosocial unconventionality. Several challenges emanate from this issue, including risk behavior-sexual intercourse. This research aims to describe the adolescents’ risk behavior-sexual intercourse in Makassar City. Design and Methods: The study uses a narrative qualitative approach with a criterion sampling technique. Three adolescents who participated in this research: two males and one female, between 17 and 19 years of age. The data are obtained through an in-depth interview based on the guideline from to Adolescent Health and Development Questionnaire by Jessor. Results: The result shows that risk behavior such as premature sexual intercourse is caused by high risk factors, including behavior, opportunity, models, and vulnerability risks. The moderator effect of protection form protective factors, such as behavior, controls, models protection and supports protections toward risk factors, play less significant roles in minimizing the possibility of indulging in risk behavior in sexual intercourse and in dating. Conclusions: The risk of sexual intercourse starts from dating, which leads to sexual intercourse. Additionally, this issue is also attributed to the risk and protective factors, affecting preparation for adulthood, personal development, and health